Analisis Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan KDRT Perspektif Sadd Aż-Żarî’ah - Mustika Septi Handini; Salis Irvan Fuadi (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2018)
Analysis of Law No. 23 of 2004 using the theory of Sadd aż-Żarîah that in Article 5 describes the ban in domestic violence. This article is very effective, because this article contains more detailed prohibition on restrictions that should not be donein the household, so not only commit acts of violence in the physical, but also covers psychological violence, sexual violence, as well as neglect of household. In Act No.23 of 2004 is in accordance with the theory of adh-dzariah sad because in setting the legal notice at the end result. Review of the result of an act, rather than taking into account the intention of the perpetrator, but that counts is the result and thefruit of such actions. Although the action aims to justify the behavior of the husband and wife are wrong, but this action will result in misery or suffering physical, sexual, psychological and neglect household, then such actions are prohibited, inaccordance with the rules of uṣûl fiqh: